Assessing Experiences with Online Educational Videos: Converting Multiple Constructed Responses to Quantifiable Data - Harrison, David J (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
Online educational videos disseminated content for a university pre-service teacher internship program. Placed within an online course management system, the videos were accessed by 202 interns located in several Western U.S. states. To ascertain the interns’ subjective experiences of the online course and videos to assist in the evaluation of the course, the researcher analyzed qualitative survey data in the form of constructed response items using a new qualitative-to-quantitative protocol. Based on phenomenological and grounded theory methods, this protocol was designed to handle the large amount of subjective constructed responses, allowing the inductive understanding of the overall experiences of a common phenomenon. The responses provided critical information that is useful for instructional designers, online educators, and educational video producers. The data suggest: 1) Universities must carefully consider video hosting options to ensure access. 2) Online videos should be carefully planned to create high quality, concise videos of less than ten minutes in length, yet contain enough educational content to reduce the overall number of required videos. 3) Students appreciate the flexibility online course delivery offered in terms of scheduling and eliminating the need to come to campus to attend seminars. 4) Self-paced online courses require progress indicators to alleviate confusion.